Treatment with Tau fibrils impact Huntington's disease-related phenotypes in cell and mouse models - Shireen Salem; Melanie Alpaugh; Martine Saint-Pierre; Flavia Natale Alves-Martins-Borba; Catalina Cerquera-Cleves; Mado Lemieux; Soki Bradel Ngonza-Nito; Paul De Koninck; Ronald Melki; Francesca Cicchetti (Neurobiology of Disease)
There is now compelling evidence for the presence of pathological forms of Tau in tissues of both patients and animal models of Huntington's disease (HD). While the root cause of this illness is a mutation within the huntingtin gene, a number of studies now suggest that HD could also be considered a secondary tauopathy. However, the contributory role of Tau in the pathogenesis and pathophysiology of this condition, as well as its implications in cellular toxicity and consequent behavioral impairments are largely unknown. We therefore performed intracerebral stereotaxic injections of recombinant human Tau monomers and fibrils into the knock-in zQ175 mouse model of HD. Tau fibrils induced cognitive and anxiety-like phenotypes predominantly in zQ175 mice and increased the number and size of insoluble mutant huntingtin (mHTT) aggregates in the brains of treated animals. To better understand the putative mechanisms through which Tau could initiate and/or contribute to pathology, we incubated StHdh striatal cells, an in vitro model of HD, with the different Tau forms and evaluated the effects on cell functionality and heat shock proteins Hsp70 and Hsp90. Calcium imaging experiments showed functional impairments of HD StHdh cells following treatment with Tau fibrils, as well as significant changes to the levels of both heat shock proteins which were found trapped within mHTT aggregates. The accumulation of Hsp70 and 90 within aggregates was also present in mouse tissue which suggests that alteration of molecular chaperone-dependent protein quality control may influence aggregation, implicating proteostasis in the mHTT-Tau interplay.